2018
DOI: 10.1158/1078-0432.ccr-17-2344
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cytogenetically Normal Acute Myeloid Leukemia During Therapy and Relapse: An Exome Sequencing Study of 50 Patients

Abstract: Purpose: To study mechanisms of therapy resistance and disease progression, we analyzed the evolution of cytogenetically normal acute myeloid leukemia (CN-AML) based on somatic alterations. Experimental Design: We performed exome sequencing of matched diagnosis, remission, and relapse samples from 50 CN-AML patients treated with intensive chemotherapy. Mutation patterns were correlated with clinical parameters. Results: Evolutionary patterns correlated with clinical outcome. Gain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 42 publications
13
106
1
2
Order By: Relevance
“…Recently, it was reported that in AML cells after allogeneic stem cell transplantation (SCT), no relapse‐specific mutational patterns were observed . In contrast, other studies found an enrichment of WT1 mutations in AML relapse after chemotherapy as well as after SCT . Although the gain of WT1 mutations were not significant in any of the studies, combined analysis of two independent cohorts showed a significant association of WT1 mutations with relapse after SCT suggesting a common evolutionary pattern (Figure ).…”
Section: Aml Relapse After Allogeneic Stem Cell Transplantationmentioning
confidence: 87%
See 3 more Smart Citations
“…Recently, it was reported that in AML cells after allogeneic stem cell transplantation (SCT), no relapse‐specific mutational patterns were observed . In contrast, other studies found an enrichment of WT1 mutations in AML relapse after chemotherapy as well as after SCT . Although the gain of WT1 mutations were not significant in any of the studies, combined analysis of two independent cohorts showed a significant association of WT1 mutations with relapse after SCT suggesting a common evolutionary pattern (Figure ).…”
Section: Aml Relapse After Allogeneic Stem Cell Transplantationmentioning
confidence: 87%
“…Five diagnosis/remission/relapse triplets were analyzed by WES and eight diagnosis/relapse pairs were analyzed by GPS . Relapse of the largest cytogenetic subgroup of AML, patients with normal karyotype, was characterized by 50 matched diagnosis/remission/relapse triplets using WES, followed by GPS for variant validation . Very recently, Cocciardi et al described the mutational spectrum at diagnosis and relapse of NPM1 mutated AML in 129 cases using GPS of five commonly mutated genes ( DNMT3A , FLT3 , NRAS , IDH1 , and IDH2 ).…”
Section: Aml Relapse After Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Attenuation of H3K27 demethylase activity of KDM6A has also been shown to enhance tumor cell radiosensitivity (25). It is important to mention that, unlike in primary AML, low KDM6A expression has been observed in relapsed AML patients (28), which further suggests that the overall contribution of KDM6A in tumorigenesis is spatiotemporally regulated.…”
Section: Discussionmentioning
confidence: 99%